KAJIAN HISTORIOGRAFI ISLAM INDONESIA KONTEMPORER (TELAAH BUKU "ISLAM NUSANTARA: JARINGAN GLOBAL DAN LOKAL" KARYA AZYUMARDI AZRA) - Firdausi, Jamilatul; Khusna, Zakiyatul; Wasil, Moch.; Zakariyah, Irfan (Jambura History and Culture Journal, 2024)
This study examines contemporary Islamic historiography in Indonesia through the book "Islam Nusantara: Global and Local Networks" by Azyumardi Azra. The aim is to explore contemporary Islamic historiography, Azyumardi Azra's biography, and a review of the book. The method used is library research. The results indicate that contemporary Indonesian Islamic historiography introduces a new style with a multidimensional approach known as "New History," which is global and comprehensive. The book emphasizes that the history of Islam in Indonesia is inseparable from the history of Islam in other regions.